National variation in pulmonary metastasectomy for colorectal cancer. (24th January 2021) - Fenton, Hayley M.; Finan, Paul J.; Milton, Richard; Shackcloth, Michael; Taylor, John C.; Treasure, Tom; Morris, Eva J. A.
Abstract: Aim: Evidence on patterns of use of pulmonary metastasectomy in colorectal cancer patients is limited. This population‐based study aims to investigate the use of pulmonary metastasectomy in the colorectal cancer population across the English National Health Service (NHS) and quantify the extent of any variations in practice and outcome. Methods: All adults who underwent a major resection for colorectal cancer in an NHS hospital between 2005 and 2013 were identified in the COloRECTal cancer data Repository (CORECT‐R). All inpatient episodes corresponding to pulmonary metastasectomy, occurring within 3 years of the initial colorectal resection, were identified. Multi‐level logistic regression was used to determine patient and organizational factors associated with the use of pulmonary metastasectomy for colorectal cancer, and Kaplan–Meier and Cox models were used to assess survival following pulmonary metastasectomy. Results: In all, 173 354 individuals had a major colorectal resection over the study period, with 3434 (2.0%) undergoing pulmonary resection within 3 years. The frequency of pulmonary metastasectomy increased from 1.2% of patients undergoing major colorectal resection in 2005 to 2.3% in 2013. Significant variation was observed across hospital providers in the risk‐adjusted rates of pulmonary metastasectomy (0.0%–6.8% of patients). Overall 5‐year survival following pulmonary resection was 50.8%, with 30‐day and 90‐day mortality of 0.6% and 1.2% respectively. Conclusions: This study shows significant variation in the rates of pulmonary metastasectomy for colorectal cancer across the English NHS.